Sustainable Development Strategy of Dolok Sembelin Protected Forest: a Case Study in Pasir Tengah Village, Tanah Pinem District, Dairi Regency, Indonesia - Prinsi Rigitta; Farid Aulia (Sean Institute, 2026)
This study aims to examine community behavior in the development and management of protected forests in Pasir Tengah Village, Tanah Pinem District, Dairi Regency. The research employs a qualitative method with a phenomenological approach to explore community experiences and perspectives regarding protected forest policies and management practices. The research informants consist of local government officials and community members directly involved in forest management activities. Data were collected through literature review, field observations, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the community plays an active role in the planning and management of protected forests by utilizing natural resources in a limited, controlled, and sustainable manner. The study also highlights the crucial role of the government in ensuring effective supervision and implementing appropriate policies to prevent forest degradation and promote sustainable forest governance. These findings are expected to provide practical and theoretical contributions to improving protected forest management and enhancing community welfare through sustainable environmental conservation.